2013
DOI: 10.1007/s12032-012-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of additional cytogenetic anomalies in chronic myeloid leukemia

Abstract: Additional chromosomal abnormalities (ACAs) in Philadelphia chromosome (Ph)-positive chronic myeloid leukemia (CML) are strongly associated with disease progression, but their prognostic impact and effect on treatment response are not clear. While the onset of ACAs in Ph-negative cells during treatment has been described, their origin and clinical significance remain to be clarified. Between January 2008 and January 2011, 105 patients with Ph-positive CML were analyzed. With a median follow-up of 25.5 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…To the best of our knowledge, ACAs are associated with CML progression, and they are subdivided into major and minor routes. The major routes have proven to have a negative impact on survival and prognosis, but the minor routes have been less considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, ACAs are associated with CML progression, and they are subdivided into major and minor routes. The major routes have proven to have a negative impact on survival and prognosis, but the minor routes have been less considered.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of tyrosine kinase inhibitors (TKIs) has greatly improved the management and prognosis of CML patients, research on CML has never stopped. Current studies have found that the incidence of additional chromosomal abnormalities (ACAs) is approximately 5% in the chronic phase (CP) of CML patients, 30% in the accelerated phase (AP) and 80% in the blast phase (BP) . Hence, ACAs are considered an intrinsic factor in the progression of CML patients with a negative impact on survival and prognosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The constitutive expression of BCR-ABL leads to the unregulated production of mature myeloid cells in the bone marrow and their subsequent release into the blood (9). If untreated, CML will progress from a chronic to an accelerated phase over a number of years, prior to quickly proceeding to a terminal blast crisis phase, reminiscent of acute leukemia (10).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more targeted therapies are warranted for these patients. Blast phase is typically characterized by the accumulation of additional chromosomal abnormalities (ACAs), but epigenetic regulation is also disrupted (reviewed also in Bozkurt et al, 2013b). While epigenetic changes occurring in CP-CML and in the progression to BP-CML have been studied extensively, changes occurring within the LSC compartment during disease progression are poorly understood and warrant further study.…”
Section: Epigenetic Mechanisms In CML Disease Progressionmentioning
confidence: 99%